Ibn Abd Rabbu Al-Andalusi and his literary efforts through Al\qid Al-Farid - Bashir, Taj Assir (Tanjong Malim, 2020)
Ibn Abd Rabbu Al-Andalusi and his literary efforts through Al\qid Al-Farid by Bashir, Taj Assir